PRAKTIK BELAJAR DAN PEMBELAJARAN BULLYING PADA SISWA KELAS V SD INPRES TAMAMAUNG III - Dina Ulandari; Astiti Tenriawaru Ahmad; M Ahkam Alwi; Amirah Aminanty Agussalim; Suasanti Suasanti; Satriani Satriani (Universitas Negeri Makassar, 2023)
Bullying is a form of negative behavior that is carried out by individuals to show their strength or want to be recognized as powerful by carrying out unfavorable actions such as hitting, mocking, frightening and suppressing other people. To overcome this problem, learning and teaching practices were carried out for fifth grade students at SD Inpres Tamamaung III. The purpose of carrying out learning and learning practice activities is to help (1) students understand what bullying means, (2) know the types or forms of bullying, (3) know the impact of bullying behavior, (4). introducing students to the factors that cause bullying behavior, (5) provide an overview of how to fight if bullying occurs. The method used is the presentation method, and to find out the results of practice are measured by giving a pretest and posttest. Based on the results obtained, it was stated that the provision of material about bullying behavior can increase students' understanding of bullying behavior.